Approaches to anticipatory governance in West Africa: How conceptions of the future have implications for climate action in the present. (August 2022) - Muiderman, Karlijn
Abstract: Methods and tools to anticipate futures are growing in prominence to guide decision-making under climate change. A research agenda into the steering effects of these processes is growing but has largely ignored how imagined futures impact present-day actions beyond the Global North. This paper presents a case study analysis of anticipatory governance in a highly climate-vulnerable area - West Africa. It examines processes of anticipation through an analytical framework that identifies four distinct approaches to anticipatory governance in terms of their conceptualization of the future, implications for actions in the present, and ultimate aims intended to be realized. The study finds two dominant approaches that appear in hybrid forms which are quite technocratic in character. These hybrids assess probable or plausible futures to inform and build capacities for strategic risk reduction. Many anticipation processes are participatory, but often focus on transferring expert-based knowledge to stakeholders or discussing adaptation options rather than opening up dialogue on what and whose futures to engage with. The paper argues that more plural and critical dialogue is needed in which stakeholders have agency to shape futures and address power imbalances, particularly in these contexts where anticipation relies on western funding and science. Highlights: There are very different ideas of how to know and govern futures in the present. Suggestions for actions in the present are quite technocratic and linear. Anticipation largely relies on western funding, science and technologies. International involvement is presented as technical assistance and apolitical. Plural and critical anticipation is missing to open up and democratize futures.